Factors that provide protection against intimate partner physical violence among married adolescents in Bangladesh - Rahman, Mizanur; Jamil, Kanta; Nahar, Quamrun; Chakraborty, Nitai; Haider, M. Moinuddin; Khan, Shusmita (Frontiers in Public Health, 2023)
Background Intimate partner violence (IPV), and especially intimate partner physical violence (IPPV), perpetrated by husbands, and within adolescence marriage are pervasive in Bangladesh. Younger women are more vulnerable to IPPV. Objectives We examined factors associated with IPPV experienced by married adolescents ages 15–19 and tested four hypotheses: (1) adolescent girls married to relatively older husbands, (2) adolescents living in extended families with parents or parents-in-law, (3) adolescents who are minimally controlled by husbands, and (4) adolescents who have a child after marriage are protective of IPPV. Methods We analyzed IPPV data from 1,846 married girls ages 15–19 obtained from a national adolescent survey conducted in 2019–20. IPPV is defined as the respondent having physical violence perpetrated by her husband at least once in the last 12 months. We implemented logistic regression models to test our hypotheses. Results Sixteen percent of married adolescent girls experienced IPPV. Girls living with parents-in-law or parents had adjusted odds ratio (AOR) of 0.56 (p < 0.001) of IPPV compared to those girls who lived with husband alone. Girls with husbands ages 21–25 years and 26 years or older had AORs of 0.45 (p < 0.001) and 0.33 (p < 0.001) of IPPV compared to those girls with their husband ages 20 and younger. Married adolescent girls who did not own a mobile phone (an indicator of spousal power dynamics) had an AOR of 1.39 (p < 0.05) compared to those girls who had a phone. IPPV risk increases with an increased duration of marriage for those with no living children (p < 0.001) but not for those with at least one living child; the risk was higher among those who had a child within the 1st year of marriage than those who had not yet had a child. At a duration of 4 years and longer, IPPV risk was higher among those with no living children than those with children. Discussion Findings related to those living with parents-in-law or parents, girls married to relatively older boys/men, having the ability to communicate with outside world, and having a child are protective of IPPV in Bangladesh are new, to our knowledge. Strictly adhering to the law that requires men waiting until the age of 21 to marry can reduce married girls' risk of IPPV. Raising girls' legal marriage age can minimize adolescents' IPPV and other health risks associated with adolescent childbearing.